Phytoplankton Productivity and Abundance in Three Main River Estuaries of Muncar Fishing Harbor, Banyuwangi, East Java, Indonesia - Lutviana Dewi; Alin Asyabil; Rahmi Valina; Damai Diniariwisan (Airlangga University, 2026)
The rapid development of industry and aquaculture in the coastal waters of Muncar has increased the amount of organic and inorganic pollutants entering the area. However, data on water quality in this region are rarely available. This study was conducted at three major river estuaries—Muara Kalimoro, Muara Wagud, and Muara Stail—using phytoplankton as bioindicators. Sampling was conducted over three months (March–April) using a plankton net (25-mesh size). This study identified four classes of phytoplankton: Chlorophyceae (2 genera), Bacillariophyceae (5 genera), Cyanophyceae (1 genus), and Eustigmatophyceae (1 genus). During observations in March, the highest variation and evenness indices (1.69 and 1.06) were recorded at Stations 3 and 2, respectively (0.94 and 0.86). However, in February and March, the highest dominance index was recorded at Stations 2 and 3, with Chlorella being the most abundant genus at all three locations, at 31,250 L⁻¹. The Muncar River estuary was classified as moderately contaminated (β meso-saprobic). These findings indicate that dissolved organic matter content influences phytoplankton community dominance. Specifically, the continuously increasing anthropogenic nutrient load risks disrupting the stability of phytoplankton dynamics, potentially triggering single-species dominance and degrading the quality of estuarine ecosystems in tropical waters. These results suggest that phytoplankton dynamics can serve as an effective early warning system for detecting anthropogenic pressures in tropical estuarine ecosystems.